Autophagy in Trypanosomatids - Paul A. M. Michels; Eva Rico; Ana Brennand (Cells, 2012)
Autophagy is a ubiquitous eukaryotic process that also occurs in trypanosomatid parasites, protist organisms belonging to the supergroup Excavata, distinct from the supergroup Opistokontha that includes mammals and fungi. Half of the known yeast and mammalian AuTophaGy (ATG) proteins were detected in trypanosomatids, although with low sequence conservation. Trypanosomatids such as Trypanosoma brucei, Trypanosoma cruzi and Leishmania spp. are responsible for serious tropical diseases in humans. The parasites are transmitted by insects and, consequently, have a complicated life cycle during which they undergo dramatic morphological and metabolic transformations to adapt to the different environments. Autophagy plays a major role during these transformations. Since inhibition of autophagy affects the transformation, survival and/or virulence of the parasites, the ATGs offer promise for development of drugs against tropical diseases. Furthermore, various trypanocidal drugs have been shown to trigger autophagy-like processes in the parasites. It is inferred that autophagy is used by the parasites in an—not always successful—attempt to cope with the stress caused by the toxic compounds.